Homo patiens : approaches to the patient in the ancient world - Petridou, Georgia.; Thumiger, Chiara. (Studies in Ancient Medicine, 2016)
Homo Patiens - Approaches to the Patient in the Ancient World is a book about the patients of the Graeco-Roman world, their role in the ancient medical encounters and their relationship to the health providers and medical practitioners of their time. This volume makes a strong claim for the relevance of a patient-centred approach to the history of ancient medicine. Attention to the experience of patients deepens our understanding of ancient societies and their medical markets, and enriches our knowledge of the history of ancient cultures. It is a first step towards shaping a history of the ancient patient's view, which will be of use not only to ancient historians, students of medical humanities, and historians of medicine, but also to any reader interested in medical ethics.